Continued breastfeeding may contribute to anemia in Peruvian children under five of indigenous households - López Huamanrayme, Eddy (2016)
We read with interest the article published by Flores-Bendezú et al (1), where it is mentioned that the prevalence of anemia in children under 5 years of indigenous households was 47.5%, highlighting that all children under 12 months had anemia, considered as possible causes poor eating foods rich in iron and enteroparasitosis (1).